ОВРАЖНАЯ ЭРОЗИЯ В ДОЛИНЕ РЕКИ РАМЕНКИ (Г. МОСКВА) В ПРОШЛОМ И НАСТОЯЩЕМ - Любимов Б.П. (My University, 2003)
History of gully network formation in the Ramenka river basin is closely connected with the history of agricultural land development of Moscow suburbs, with the housing and industrial building activity, road constructing, and city planning in the recent time. The author retraced generation, growth and degradation of gullies by comparing old and new maps and providing special field-works. The gully systems are still active and new gullies are rising nowadays, even in the condition of complete urban redevelopment. It should be taken into account while planning to transform the Ramenka valley into recreation area and natural monument.
Keywords: 551.435.162(470.311)